2011
DOI: 10.1161/atvbaha.110.221879
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Protein Kinase C-θ Deficiency With Human RUNX1 Mutation

Abstract: Objective Mutations in hematopoietic transcription factor RUNX1 cause thrombocytopenia and impaired platelet function. In a patient with a heterozygous mutation in RUNX1 we have described decreased platelet pleckstrin phosphorylation and protein kinase C-θ (PKC-θ, gene PRKCQ) associated with thrombocytopenia, impaired platelet aggregation, and dense granule secretion. Little is known regarding regulation of PKC-θ in megakaryocytes/platelets. We have addressed the hypothesis that PRKCQ is a direct transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Moreover, our expression profiling studies in the same patient showed that a wide array of genes involved in platelet function and formation are downregulated [8]. We have shown that several relevant genes including PRKQ [9] , MYL9 [10], ALOX12 [12], PLDN [24] and PCTP [25] are direct transcriptional targets of RUNX1. Thus, we postulate that the secretory abnormalities result from aberrations in common pathways critical to the general process of exocytosis, for example, involving vesicle transport mechanisms, Rab proteins, and SNARE proteins [16, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our expression profiling studies in the same patient showed that a wide array of genes involved in platelet function and formation are downregulated [8]. We have shown that several relevant genes including PRKQ [9] , MYL9 [10], ALOX12 [12], PLDN [24] and PCTP [25] are direct transcriptional targets of RUNX1. Thus, we postulate that the secretory abnormalities result from aberrations in common pathways critical to the general process of exocytosis, for example, involving vesicle transport mechanisms, Rab proteins, and SNARE proteins [16, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abnormalities in mechanisms that regulate secretion have been reported in some patients [2, 3, 5], including in myosin light chain and pleckstrin phosphorylation, and decreased platelet PKC-θ [6, 7]. Platelet mRNA expression profiling of a patient with RUNX1 mutation [8] and other studies [7] have shown downregulation of several genes, including MYL9 , PRKQ ALOX12 and PF4, and some of these are direct transcriptional targets of RUNX1, providing evidence for aberrations in multiple platelets mechanisms, including in those regulating platelet responses to activation [2, 912]. …”
Section: Introductionmentioning
confidence: 99%
“…In our platelet transcript profiling studies of a patient with RUNX1 mutation numerous genes relevant to multiple platelet biological pathways were downregulated. 33 Several genes have been shown to be direct transcriptional targets of RUNX1, including 12-lipoxygenase ( ALOX12 ), 25 platelet factor 4 ( PF4 ), 34 platelet myosin light chain ( MYL9 ), 35 protein kinase C-θ ( PRKCQ ), 36 palladin ( PLDN ), 26 and the thrombopoietin receptor ( c-MPL ). 37 These impact various aspects of MK biology, platelet production, structure, signaling, and responses.…”
Section: Runx1mentioning
confidence: 99%
“…RUNX1 targets involved in decreased platelet production include the genes for the MPL receptor (MPL) [11], myosin IIA (MYH9), myosin IIB (MYH10), and myosin regulatory light chain (MYL9) [10]. Besides MYL9, other RUNX1 target genes with a role in platelet function have been found, by platelet expression profiling, to be downregulated in one FPD/AML patient; these included the genes for platelet 12-lipoxygenase (ALOX12) and protein kinase C-h (PKCh) [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%